FACTOR ANALYSIS OF WEB-BASED IDEA MANAGEMENT SYSTEM APPLICATION RESULTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
the aim of the study is to reveal the underlying factors from variable data collected on the results of the web-based ideas management systems related to management and tangible results in companies. The purpose of the factor analysis process is to collect the information contained in a large number of changes in such a way as to obtain latent factors with minimal data loss. Authors have conducted global survey for enterprises that apply these systems (n>500). The 8 variables that fit together reveal the latent factor “tangible” or tangible results and the remaining 6 variables that together reveal the latent factor “managerial” or the management results.